THE INNOVATIVE DIRECTIONS IN ECONOMIC EDUCATION - Fedotova, I.A. (Perm Federal Research Centre Journal, 2016)
This article is devoted to the analysis of innovative directions in the sphere of economic education. The use of mechanisms of network in education includes three main components: planning, instruction, and evaluation. The main elements of the structure are as follows: innovation systems in education in the form of social organizations, social communities (teachers and learners), the process of learning as a kind of social and cultural activity, the objective status of professionals, the complex of roles associated within a certain social institution. The social norm is assigned to measure the standard for individuals behavior, their activity evaluation and the development of innovation methods.